Comparison of GaN/AlGaN/AlN/GaN HEMTs Grown on Sapphire with Fe-Modulation-Doped and Unintentionally Doped GaN Buffer： Material Growth and Device Fabrication - 巩稼民 王权 闫俊达 刘峰奇 冯春 王晓亮 王占国 (Chinese physics letters, 2016)
AlGaN/GaN high electron mobility transistors （HEMTs） grown on Fe-modulation-doped （MD） and unintentionally doped （UID） GaN buffer layers are investigated and compared. Highly resistive GaN buffers （10^9Ω·cm） are induced by individual mechanisms for the electron traps＇ formation： the Fe MD buffer （sample A） and the UID buffer with high density of edge-type dislocations （7.24×10^9cm^-2, sample B）. The 300K Hall test indicates that the mobility of sample A with Fe doping （2503cm^2V^-1s^-1） is much higher than sample B （1926cm^2V^-1s^-1） due to the decreased scattering effect on the two-dimensional electron gas. HEMT devices are fabricated on the two samples and pulsed I–V measurements are conducted. Device A shows better gate pinch-off characteristics and a higher threshold voltage （-2.63V） compared with device B （-3.71V）. Lower gate leakage current ｜IGS｜ of device A （3.32×10^-7A） is present compared with that of device B （8.29×10^-7A）. When the off-state quiescent points Q_2 （V GQ2=-8V, V DQ2=0V） are on, V th hardly shifts for device A while device B shows ＋0.21V positive threshold voltage shift, resulting from the existence of electron traps associated with the dislocations in the UID-GaN buffer layer under the gate. Under pulsed I–V and transconductance G m–V GS measurement, the device with the Fe MD-doped buffer shows more potential in improving reliability upon off-state stress.